Carbon Acidity in Enzyme Active Sites - Toney, Michael D. (Frontiers in Bioengineering and Biotechnology, 2019)
The pKa values for substrates acting as carbon acids (i.e. C-H deprotonation reactions) in several en-zyme active sites are presented. The information needed to calculate them includes the pKa of the active site acid/base catalyst and the equilibrium constant for the deprotonation step. Carbon acidity is obtained from the relation pKeq = pKar – pKap = deltapKa for a proton transfer reaction. Five enzymatic free energy profiles were calculated to obtain the equilibrium constants for proton transfer from carbon in the active site, and six additional proton transfer equilibrium constants were extracted from data available in the literature, allowing substrate C-H pKas to be calculated for eleven enzymes. Active site-bound substrate C-H pKa values range from 5.6 for ketosteroid isomerase to 16 for proline racemase. Compared to values in water, enzymes lower substrate C-H pKas by up to 23 units, corresponding to 31 kcal/mol of carbanion stabilization energy. Calculation of Marcus intrinsic barriers for pairs of nonen-zymatic/enzymatic reactions shows significant reductions in deltaGint for cofactor-independent enzymes, while pyridoxal phosphate dependent enzymes appear to increase deltaGint to a small extent as a conse-quence of carbanion resonance stabilization.